Pasjonujące praskie leporello. Praga, niespokojne serce Europy (1984) Very Chytilovej - Hucko, Tomas (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
Exciting Prague Leporello. Prague, the Restless Heart of Europe (1984), a film by Věra Chytilová Věra Chytilova’s film was created during the culmination of processes related to the Czechoslovak normalization. Prague… is not only a highly stylized film essay that provides the viewer with a fascinating visual experience and deep emotions, but evokes the themes of a substantive philosophical debate in conjunction with the knowledge of Prague’s genius loci. Chytilova’s film considers the history and role of humans, taking as a starting point the history of Prague. Therefore, the film still inspires. Film Věry Chytilovej powstał w latach kulminacji procesów związanych z czechosłowacką normalizacją. Praga… jest nie tylko wysoce stylizowanym esejem filmowym, który dostarcza widzowi fascynację wizualną i głębokie emocje, przedstawia także debatę merytoryczną natury filozoficznej w powiązaniu ze świadomością praskiego genius loci. Biorąc za punkt wyjścia historię Pragi, rozważa dzieje i rolę człowieka w nich. Dlatego film ten do dziś inspiruje.